Endovascular Repair of Symptomatic Right Subclavian and Innominate Artery Aneurysms Arising From a "Bovine Arch" in a Patient With a "Hostile" Chest. (April 2021) - Mukherjee, Dipankar; Lewis, Elizabeth; Ryan, Liam
Symptomatic aneurysms of the innominate and subclavian arteries are rare and pose unique challenges for endovascular repair particularly in a patient with a "bovine" arch. Previous publications have described back table modifications of standard iliac endografts to conform to the innominate artery for exclusion of the lesion. Others have proposed extra-anatomic bypass or carotid-subclavian transposition with occlusion of the innominate artery. We were unable to find a report of repair when aneurysms of the innominate and subclavian arteries were in continuity. We present such a case of endovascular repair using commercially available endografts without compromise of the left common carotid artery origin as this patient had a "bovine" arch. Surgeons will benefit from adding this endovascular option to their "tool box" when confronted with such a challenging clinical scenario.